KEPEMIMPINAN KARISMATIK SEBAGAI EMPLOYER BRANDING - Ria Marginingsih (Institut Informatika Dan Bisnis (IIB) Darmajaya, 2016)
Charismatic leadership is a type of leadership that can influence the values of its members. This research is aimed at looking at employer branding factors from charismatic leadership based on member's perceptions based on generations (generations X and Y) and gender (male and female). Based on the independent t-test independent test results, the results of this study indicate that there are significant differences based on generation and gender in the charismatic leadership dimensions. Based on the gender of male employees have a more positive perception on the dimensions of self-confidence, motivating inspiration and ideal influences, while female employees have a more positive perception of the dimensions of individual consideration and intellectual knowledge. By age, early adolescents and early adolescents have the highest perception of ideal effects dimensions, the final adult employees and employees over 45 have the highest perception of the dimension motivating.Keywords: Charismatic Leadership, Employer Branding, Gender, Generation X and Y, Leadership Style.